Preliminary report of transfrontier disease surveillance in free-ranging buffalo in the Caprivi Strip, Namibia - Massimo Scacchia; Mark Jago; Rossella Lelli; Anna Marais; Andrea Capobianco Dondona (Veterinaria Italiana, 2010)
A capture operation to ascertain the health status of free-ranging buffalo (Syncerus caffer) from six areas in the Caprivi Strip in the north-east corner of Namibia is described. In-depth reports on buffalo capture operations and their cost, with detailed descriptions of diseases for research purposes, sampling techniques, field processing of samples and laboratory-related costs are still lacking in the literature. This paper describes materials, methods and the related costs of a disease surveillance operation conducted among buffalo in Namibia. The survey attempted to provide information designed to improve the control of infectious diseases in the Caprivi Strip, a key area bordering Angola, Zambia, Botswana and Zimbabwe.